Effects of dietary Cu, Zn, and ractopamine-HCl on finishing pig growth performance, carcass characteristics, and antimicrobial susceptibility of enteric bacteria - Feldpausch, J. A.; Amachawadi, Raghavendra; Tokach, Michael D.; Scott, H. M.; Dritz, Steven S.; Nagaraja, Tiruvoor G.; Goodband, Robert D.; Woodworth, Jason C.; DeRouchey, Joel M. (My University, 2016)
A total of 480 pigs (PIC 327 × 1050; initially 48.7 kg) were used to determine the interactive effects of supplemental Cu, Zn, and ractopamine HCl on finishing pig growth, carcass characteristics, and antimicrobial susceptibility of enteric bacteria. Treatments were arranged in a 2 × 2 × 2 factorial with main effects of added copper (CuSO4; 0 vs. 125 ppm Cu), added zinc (ZnO; 0 vs. 150 ppm Zn) and ractopamine HCl (0 vs. 10 ppm during the last 28 d before marketing; Paylean®; Elanco Animal Health, Greenfield, IN). All diets contained 11 ppm Cu and 73 ppm Zn from the trace mineral premix. Pens of pigs were balanced and blocked on initial BW then randomly allotted to 1 of the 4 mineral treatment diets. Twenty-eight d before marketing, pens within each block and mineral treatment were randomly assigned to receive either 0 or 10 ppm ractopamine in addition to the mineral treatment. Adding either Cu or Zn alone did not improve ADG or ADFI yet resulted in numerical improvements in overall G:F and caloric efficiencies but improvements were not additive (Cu × Zn, P = 0.057, 0.068 and 0.064 for G:F and caloric efficiency on a ME and NE basis, respectively). Ractopamine improved (P < 0.001) overall ADG, G:F, and caloric efficiency thereby increasing final BW by 3% with no change in ADFI. Ractopamine increased (P < 0.001) HCW, percent carcass yield, HCW G:F, loin depth, and percent fat-free lean and decreased (P = 0.014) backfat. An interaction existed whereby adding Zn or Cu alone to diets containing ractopamine numerically improved percent carcass yield and HCW G:F, but no improvement was observed when the Cu or Zn was added to the control diet or when Cu and Zn were fed in combination in the ractopamine diets (Cu × Zn × ractopamine, P = 0.011 and 0.018 for yield and HCW G:F, respectively). Fecal samples were collected on d 0 and at the conclusion of the finishing period (d 90) for bacterial isolation and antimicrobial susceptibility determinations according to minimal inhibitory concentration breakpoints. Escherichia coli and Enterococcus spp. isolates displayed varying levels of resistance to certain antibiotics before initiation of treatments on d 0. Resistance to most antibiotics decreased (P < 0.05) over time or was stable for those that had a low base-line percentage of resistance. Ractopamine and Zn did not adversely affect antimicrobial resistance but extended feeding of 125 ppm Cu throughout the finishing period appeared to antagonize any time-associated decrease in enterococcal resistance to tetracycline, tylosin, and quinupristin/dalfopristin.
Citation: Feldpausch, J. A., Amachawadi, R., Tokach, M. D., Scott, H. M., Dritz, S. S., Nagaraja, T. G., . . . DeRouchey, J. M. (2016). Effects of dietary Cu, Zn, and ractopamine-HCl on finishing pig growth performance, carcass characteristics, and antimicrobial susceptibility of enteric bacteria. Journal of Animal Science, 94, 73-74. doi:10.2527/msasas2016-157
Keywords: Finishing Pig; Mineral; Antimicrobial Resistance; Agriculture